Inclusive Educational Ethics, Facing the Facts - Deyrich, Marie-Christine; Magdalena Kohout-Diaz (Educational Research E-Books Online, Collection 2024., 2024)
This book takes the reader on a journey through different national contexts. Discover the unique challenges and strategies for inclusive education in countries such as Romania, Poland, Guadeloupe and Canada. Explore the need for independent living skills for institutionalised children in Romania, the paradoxes of educational inclusion for Ukrainian refugees in Poland, and the impact of teacher communication styles on student motivation in Guadeloupe. The negotiation of teacher education policy and standards in Canada is also on the agenda. For anyone with a passion for inclusive education, this book is a treasure trove of information. Contributors are: Laura Agrati, Daniela Roxana Andron, Stephanie Arnott, Dorota Bazuń, Maria Chatzi, Cheryl J. Craig, Stella Danou, Marie-Christine Deyrich, Amen Dhahri, Panagiota Diamanti, Heidi Flavian, Joanna Frątczak-Müller, Becca Friesen, Robert Grant, Josh Gray, Elisabeth Issaieva, Axelle James, Stavroula Kaldi, Adam Kaszuba, Ștefania Kifor, Magdalena Kohout-Diaz, Mariusz Kwiatkowski, Pascal Legrain, Mimi Masson, Anna Mielczarek-Żejmo, Patricia-Gabriela Mociar, Fernando Naiditch, Carrie Nepstad, Frances Rust, Sophie Sanchez-Larréa, Fiona Smythe, Martin Strouhal, Vassiliki Tzika, Aikaterini Vassiou, Efstathios Xafakos and Diane Yendol-Hoppey.